Analisis Keberlanjutan Taman Wisata Alam Lembah Harau di Kabupaten Lima Puluh Kota - Yolanda, Putri; Soekmadi, Rinekso; Prihadi, Nandang; Adhi, Rizky Pratama (Jurnal Teknologi Lingkungan, 2024)
Lembah Harau Nature Tourism Park (TWA) is one of the natural tourism potentials in Lima Puluh Kota Regency with an area of 27.5 Ha. Based on statistical data in 2022, there will be an increase in tourists from TWA Lembah Harau in Lima Puluh Kota Regency, with a recorded increase in tourists reaching 14% with the number of visits in 2022 amounting to 270,790 visitors. Increasing Lembah Harau TWA visits can have a positive impact on increasing income for both the community and the government, however if it exceeds the area's carrying capacity it can cause negative impacts on the ecological aspects of the surrounding area. Based on this, the concept of regional development strategy is an important factor in developing sustainable tourism activities. This research was conducted from November to December 2022. The aim of this research is to analyze the strategy for sustainable development of the Lembah Harau TWA. Data collection was carried out to identify the carrying capacity of each tourist attraction and development analysis using SWOT (Strength-Weakness-OpportunitiesThreats) with interviews with certain stakeholders. The results of the overall carrying capacity analysis of the Lembah Harau TWA area can accommodate 313,337 visitors per year or 2,725 visitors per day. Based on the results of the carrying capacity analysis for each tourist attraction unit, it is stated that tourists can be accommodated to carry out activities in the area. So, the main strategy for sustainable development is to optimize the Lembah Harau TWA by expanding areas that have the potential for waterfalls as the main tourist attraction by optimizing the infrastructure of the Lembah Harau TWA.   Abstrak Taman Wisata Alam (TWA) Lembah Harau merupakan salah satu potensi wisata alam di Kabupaten Lima Puluh Kota dengan luas 27,5 Ha. Berdasarkan data statisik tahun 2022 terjadi peningkatan wisatawan TWA Lembah Harau di Kabupaten Lima Puluh Kota, tercatat kenaikan wisatawan mencapai 14% dengan jumlah kunjungan tahun 2022 sebesar 270.790 pengunjung. Peningkatan kunjungan TWA Lembah Harau dapat menimbulkan dampak positif bagi peningkatan pendapatan baik masyarakat maupun pemerintah, namun apabila telah melampaui daya dukung kawasan dapat menyebabkan terjadinya dampak negatif terhadap aspek ekologi kawasan sekitar. Berdasarkan hal tersebut, maka konsep strategi pengembangan kawasan menjadi faktor yang penting dalam pengembangan kegiatan wisata yang berkelanjutan. Penelitian ini dilakukan dari bulan November hingga Desember 2022, Adapun tujuan penelitian ini adalah menganalisis strategi pengembangan TWA Lembah Harau yang berkelanjutan. Pengumpulan data dilakukan untuk mengidentifikasi daya dukung setiap atraksi wisata hingga analisis pengembangan menggunakan SWOT (StrengthWeakness Opportunities-Threats) dengan wawancara pada stakeholder tertentu. Hasil analisis daya dukung secara keseluruhan kawasan TWA Lembah Harau dapat menampung 313.337 pengunjung pertahun atau 2.725 pengunjung perhari. Berdasarkan hasil analisis daya dukung tersebut untuk setiap unit atraksi wisata, dinyatakan bahwa wisatawan dapat ditampung untuk melakukan kegiatan/aktivitas di area tersebut. Maka, strategi utama pengembangan berkelanjutan yang dilakukan dengan mengoptimalkan TWA Lembah Harau dengan perluasan kawasan yang memiliki potensi air terjun sebagai daya tarik utama wisata dengan mengoptimalkan sarana prasarana TWA Lembah Harau.